Drug abuse and ACS in the very young (less than 30 years): Demographic, clinical and angiographic profile - Shibba Takkar Chhabra; Gurleen Kaur; Samir Kapoor; Aastha Kapila; Gagandeep Kaur; Prannav Jain; Pankaj kumar; Namita Bansal; Mamta Bansal; Anshuman Gupta; Akash Batta; Gautam Singal; et al. (Indian Heart Journal)
Aim: To identify incidence, type of drug abuse study clinical and angiographic profile in very young population presenting with acute coronary syndrome (ACS). Materials and methods: All consecutive patients less than 30 years with ACS included and segregated into Group 1 and 2 (with and without drug abuse respectively) Result: n = 153; n = 17 in group 1 of whom 35.29 % consumed opium, 17.64 % energy drinks, 17.64 % whey protein supplements, 17.64 % inhaled marijuana, 5.88 % heroin and spasmoproxyvon and 23.52 % multi-substance abusers. STEMI, Single vessel disease and urban domicile were predominant. Rising trends of drug abuse were identified in prospective (28.20 %) versus retrospective (5.30 %) timeframe (p = 0.011). Conclusion: Rising trends of drug abuse, a potentially modifiable risk factor of ACS in the young are alarming. Strict regulations are needed to curb this menace.